Should We Postpone Elective Cardiovascular Procedures and Percutaneous Coronary Interventions During the COVID-19 Pandemic? - Keskin, Gokhan; Khalil, Emced; Uysal, Ayhan (Forum Multimedia Publishing, Llc, 2021)
Background: Prioritization among patients with coronary artery disease represents a difficult issue during the SARS-CoV-2 pandemic. We present our clinical practices and patients' outcomes after elective, emergent and urgent cardiovascular surgery and percutaneous coronary interventions (PCI). We also investigated the rate of nasocomial infection of SARS-CoV-2 in health workers (HWs), including surgeons after cardiovascular procedures and percutaneous interventions (PCI). Material and methods: We performed 186 cardiovascular operations and PCI between March 15 and October 15. According to level of priority (LoP), we performed urgent and emergent coronary artery bypass grafting (CABG) and cardiac valve repair or replacement surgery in 44 patients. In one patient with acute chordae rupture with pulmonary edema, we performed mitral valve replacement. We performed aortic arch repair in two patients with type-I aortic dissection in urgent situations. Therefore, in 47 patients we performed cardiac operations in urgent or emergent situations. Elective CABG (N = 28) and elective cardiac valve (N = 10) surgeries were performed (total: 38). While rescue PCI were urgently performed in 47 patients with ST segment elevation myocardial infarction ( STEMI), it was performed in elective or emergent situations in 40 patients with myocardial ischemia. Endovascular treatment was performed in four patients with deep venous thrombosis (DVT) and in four patients with chronic arterial occlusion, respectively. Surgical vascular repair and embolectomy were performed in patients with peripheral artery injury (N = 6) and acute arterial embolic events (N = 4), respectively. We performed thoracic computed tomography followed by reverse transcriptase-polymerase chain reaction (RT-PCR) test in patients with irregular diffuse reticular opacities with or without consolidation on chest X-ray. Blood coagulation disorders including d-dimer, thromboplastin time (TT), and partial thromboplastin time (aPTT) were measured prior to procedures. Results: No mortality and morbidity was seen after percutaneous and surgical arterial or venous procedures. Total mortality rate was 4.1% (8 of 186 CAD patients or valve surgery) after urgent and emergent CABG (N = 4), an urgent valve replacement (N = 1), and PCI (N = 3). Low cardiac output syndrome (LOS) and major adverse cardiac cerebrovascular event (MACCE) were the mortality factors after cardiac surgery. The reasons for death after PCI were sudden cardiac arrest related to dissection of the left main coronary artery during procedure and pneumonia due to COVID-19 (N = 2). Ground-glass opacities in combination with pulmonary consolidations was detected in seven patients. Interlobular septal and pleural thickening with patchy bronchiectasis in the bilateral lower lobe involvement was found after thoracic computed tomography in these patients. We confirmed in-hospital COVID-19 using PCR test in two patients with STEMI prior to PCI. PT and aPTT increased, but fibrin degradation products did not in those two patients. We confirmed COVID-19 via phone call in six CABG patients and one PCI patient after discharge from hospital. None of the patients diagnosed with COVID-19 died after being discharged from the hospital. Conclusion: Cardiovascular surgery and PCI can safely be performed with acceptable complications and mortality rates in elective situations, during the COVID-19 pandemic. Preoperative control of OR traffic, careful evaluation of the patient's history, consultation, and precautions taken by healthcare professionals are important, during and after procedures. Also important is the wearing a mask and face shield and careful disinfection of equipment and space.
Keywords: Cardiac-Surgery; Anxiety